(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
Through out examination of 162 fish common carp Cyprinus carpio from cages breeding fish in Euphrates River, AL-Mussaib, Babylon. The total percentage of infection and intensity of internal parasites was 13.56% the percentage 4.27 of infection with Bethriocephaius opseriichthyolrs, The percentage with Gryprophychu cheileaucristrtus 12.96% and intensity infection 4.38, Gryprophychu ligula the percentage 11.0% and intensity infection 3.9, Proteacephlus osculates The percentage 9.25% and intensity infection 4.73, Neoechinorhynchus agilis The percentage 12.34% and intensity infection 4.65, and Neoechinohychus iraqensis the percentage 12.96% intensity infection 5.28, The percentage in cidence of infection with the studied parasites varied according in different months.